Data from: Migratory culture, population structure and stock identity in North Pacific beluga whales (Delphinapterus leucas) - O'Corry-Crowe, Greg; Suydam, Robert; Quakenbush, Lori; Potgieter, Brooke; Harwood, Lois; Litovka, Dennis; Ferrer, Tatiana; Citta, John; Burkanov, Vladimir; Frost, Kathy; Mahoney, Barbara (Zenodo, 2019)
The annual return of beluga whales, Delphinapterus leucas, to traditional seasonal locations across the Arctic may involve migratory culture, while the convergence of discrete summering aggregations on common wintering grounds may facilitate outbreeding. Natal philopatry and cultural inheritance, however, has been difficult to assess as earlier studies were of too short a duration, while genetic analyses of breeding patterns, especially across the beluga's Pacific range, have been hampered by inadequate sampling and sparse information on wintering areas. Using a much expanded sample and genetic marker set comprising 1,647 whales, spanning more than two decades and encompassing all major coastal summering aggregations in the Pacific Ocean, we found evolutionary-level divergence among three geographic regions: the Gulf of Alaska, the Bering-Chukchi-Beaufort Seas, and the Sea of Okhotsk (Φst=0.11-0.32, Rst=0.09-0.13), and likely demographic independence of (Fst-mtDNA=0.02-0.66), and in many cases limited gene flow (Fst-nDNA=0.0-0.02; K=5-6) among, summering groups within regions. Assignment tests identified few immigrants within summering aggregations, linked migrating groups to specific summering areas, and found that some migratory corridors comprise whales from multiple subpopulations (PBAYES=0.31:0.69). Further, dispersal is male-biased and substantial numbers of closely related whales congregate together at coastal summering areas. Stable patterns of heterogeneity between areas and consistently high proportions (~20%) of close kin (including parent-offspring) sampled up to 20 years apart within areas (G=0.2-2.9, p>0.5) is the first direct evidence of natal philopatry to migration destinations in belugas. Using recent satellite telemetry findings on belugas we found that the spatial proximity of winter ranges has a greater influence on the degree of both individual and genetic exchange than summer ranges (rwinter-Fst-mtDNA=0.9, rsummer-Fst-nDNA=0.1). These findings indicate widespread natal philopatry to ...